Two rTMS sessions per week: a practical approach for treating major depressive disorder. Issue 17 (28th October 2021) - Armas-Castañeda, Gabriela; Ricardo-Garcell, Josefina; Reyes, Julian V.; Heinze, Gerhard; Salín, Rafael J; González, Jorge J.
Abstract : Introduction: Depression is one of the leading causes of disability in the world, and a disease that contributes greatly to the global burden of disease. Repetitive transcranial magnetic stimulation (rTMS) has proven to be a well-tolerated, effective treatment for depression. The present study was designed to evaluate the efficacy of an rTMS treatment scheme with a fewer number of sessions per week. Methods: In total 91 adult university students with major depressive disorder (MDD). This was a double-blind, randomized clinical trial in which 15 sessions of rTMS were given to each one of two treatment groups made up of adults with active MDD. One treatment group received two sessions per week, the other received five. The study protocol included their respective sham rTMS groups. The patients who received active rTMS also participated in a follow-up procedure that consisted of two sessions of active rTMS per month for three more months. Results: Measurements by the Hamilton Rating Scale for Depression (HAMD) showed that the groups which received active rTMS had higher percentages of antidepressant response at 96 and 95.5% for five and two sessions/week, respectively, compared to the sham rTMS groups: 27.3 and 4.5% for five and two sessions/week, respectively. Observations at the end of the 3-month follow-up phase showed that the improvements in HAMD scores were maintained in both groups. Conclusion: This study contributes to demonstrating that rTMS with a more practical schedule of two sessions/week is an effective antidepressant treatment that could be considered the first choice for managing symptoms of depression.